Lisinopril Dihydrate: Single‐Crystal X‐Ray Structure and Physicochemical Characterization of Derived Solid Forms. Issue 10 (19th July 2013) - Sorrenti, Milena; Catenacci, Laura; Cruickshank, Dyanne L; Caira, Mino R.
<x xml:space="preserve">Abstract</x> Screening for new solid forms of the antihypertensive lisinopril was performed by recrystallization of the commercial form, lisinopril dihydrate, from various solvents and by exposing the product of its dehydration to a series of vapors under controlled conditions. Modifications other than the dihydrate encountered in the study included new anhydrous and amorphous forms, with intrinsic dissolution rates significantly greater than that of the dihydrate. Further physicochemical characterization included constant and programmed temperature powder X‐ray diffraction, differential scanning calorimetry, thermogravimetry, and Fourier transform infrared spectroscopy. In the course of this study, the single‐crystal X‐ray structure of lisinopril dihydrate, [a = 14.550(2), b = 5.8917(8), c = 14.238(2) Å, β = 112.832(3)° at T = 173(2) K, space group P21, Z = 2], was determined for the first time, revealing its double zwitterionic character in the solid state. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3596–3603, 2013